Development of Bigels Using Citrus Fiber and Beeswax: Application in Cocoa Spread Formulation as Palm Oil Alternative - Yilmaz, Ezgi Genc; Akcicek, Alican; Kablan, Taylan; Ozgolet, Muhammed; Karasu, Salih (WILEY, 2026)
In this study, bigel systems were developed as potential alternatives to palm oil in cocoa spreads. This study developed citrus fiber (CF)-based bigel systems as alternatives to palm oil in cocoa spreads. Bigels were formulated by combining hydrogels (HG) containing CF (5% and 7.5%) with olive oil oleogels (OG) structured using 10% beeswax at different HG:OG ratios (80:20, 50:50, and 20:80). All bigels exhibited higher storage (G ') and loss (G '') moduli than palm oil, indicating enhanced viscoelastic behavior. Increasing the oleogel fraction improved the structural integrity of the bigel network. Bigels containing 7.5% CF were incorporated into cocoa spreads, where higher oleogel ratios increased the solid character (G '). All bigel-enriched cocoa spreads showed thixotropic behavior with lower deformation and higher structural recovery compared to palm oil-based spreads. Additionally, bigel addition improved temperature-dependent stability. These results demonstrate that CF-based bigels provide a compact, viscoelastic, and stable fat system, highlighting their potential as palm oil replacers in cocoa spread formulations.
Keywords: 3-ITT; bigel; citrus fiber; cocoa spread; hydrogel; oleogel; rheology; STABILITY; Engineering; Food Science & Technology